Trends of Diabetes-Related Hospital Admission in Emerging Adults in the State of California - Nip, Angel Siu-ying (J Endocr Soc, 2021)
Background: As adolescents with diabetes transition to adulthood, they may demonstrate poorer adherence to treatment regimens and may be vulnerable to complications such as diabetic ketoacidosis (DKA) or severe hypoglycemia. A number of important factors have been identified as risk factors for these poor outcomes, including loss of health insurance coverage, increased risk-taking behaviors, and difficulty coping with added responsibility. National data may inform efforts to improve health outcomes and prevent complications for vulnerable young adults during this challenging transition to independence. Objectives: To estimate the incidence of diabetes-related admissions and to describe the characteristics among youth and young adults with type 1 (T1D) and type 2 diabetes (T2D) in the state of California. Study design and method: This is a retrospective cohort study using the inpatient database from the Office of Statewide Health Planning and Development during the years 2014 to 2018. Individuals aged 13–24 years hospitalized with DKA, or hypoglycemia, were identified by ICD codes. Results: A total 28,754 admission encounters were recorded. Mean ages for T1D and T2D were 17.3±5.6 years and 17.9±4.6 years, respectively. Hospitalization rates increased with age with a significant rise during the transition to adulthood, from 70.3/100,000 population at age 17 to 132.2/100,000 population at age 19 in T1D. Among hospital admissions in T1D and T2D, 16.3% and 18.7% were Black young adults respectively (p <.001). More young adults were on public insurance when compared to youth (64.1% vs 45.1% in T1D; 68.4% vs 50.4% in T2D, p <.001), and approximately 48.8% and 41.6% were from the lowest income quartile in T1D and T2D respectively (p <.001). There was no difference in mean length of hospital stay, but hospital charges were higher among young adults with both types of diabetes when compared to youth ($41,370 vs $36,160 in T1D; $37,218 vs $30,991 in T2D, p <.001). More young adults were admitted for severe cases such as DKA or hypoglycemia with coma in T1D, with rates tripling from 0.3/100,000 population in youth to 1.0/100,000 population in young adults. Conclusion: We demonstrated a significant rise in admission rates during the transition to adulthood in individuals with T1D. Among admissions in both types of diabetes, there were significantly more Black young adults who were on public insurance with lower socioeconomic status. This population group had poorer health outcomes with higher incidence for moderate and severe complications, and they cost more hospital charges than the youth population with both types of diabetes. Our findings suggest that the US healthcare system fails many emerging adults with diabetes, particularly for people of color, and that improving the medical transition is crucial. More resources should be focused on this at-risk population from a healthcare system perspective.